Identification of Medicinal Plants in State Islamic University of Kiai Haji Achmad Siddiq Jember - Sholihah, Nanda Amanatus; Millah, Nur; Lillah, Sarah Qonita; Pratiwi, Tiara (Aspirasi Masyarakat Intelektual Islam Nusantara, 2022)
Medicinal plants are all forms of plants that are known to possess medicinal characteristics that are effective in both promoting health and treating sickness. On the basis of human observations, these medicinal plants have been discovered and are known to have a substance that is effective for preventing and treating illness and is capable of performing certain biological functions. However, information on the sorts of medicinal plants found in the area of UIN KHAS Jember is limited. This research tries to investigate medical plant species and plant components that may be utilized as medications. The qualitative descriptive method used in this study will characterize the medicinal plants discovered (taxonomy, family morphology, parts used, and how to use them). This investigation was carried out utilizing field survey and documentation techniques. As a result, 13 families with 16 species of medicinal plants may be found near UIN KHAS Jember. There are members of the Annonaceae, Euphorbiaceae, Bromeliaceae, Solanaceae, Piperaceae, Lamiaceae, Zingiberaceae, Myrtaceae, Rutaceae, Moringaceae, Pandanaceae, Arecaceae, and Xanthorrhoeaceae families, based on the identification findings. The most abundant medicinal plants in UIN KHAS Jember is the Arecaceae family with the species name Cocos nucifera L, which way to consume it is by drinking the water.